Strategi Kesantunan dalam Tradisi Lisan Minangkabau dan Bali: Suatu Kajian Pragmatik Antarbudaya - Widya Fhitri; Ni Luh Kade Yuliani Giri; Rabbi Antaridha; Abdul Dinul Haq (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2026)
This study aims to analyze and compare language politeness in the spoken traditions of Minangkabau and Balinese communities through an intercultural pragmatics approach. One way of communication that represents the social norms and cultural principles of a society is spoken tradition. In this situation, language politeness reflects the communication strategies used by speakers to maintain social balance and respect the interlocutor. This research is a descriptive qualitative study with a pragmatic approach to identify the forms, and strategies of language politeness in the spoken traditions of both cultures. The data uses observational method and support note-taking and recording as techniques. The data will be analyzed by using Brown and Levinson's (1987) politeness theory on politeness strategies as well as relevant local perspectives in each culture by using ethnography communication. In analyzing the data, the author uses the pragmatic method, while to present the research results, formal and informal methods are used in which the results of all data analysis are presented thoroughly. What is expected from the results of the study is to increase the understanding of different language politeness strategies in spoken language between two cultures and how the dynamics of intercultural communication occur in Indonesia. In addition, the findings can be used as a reference for sosiopragmatics studies, and the preservation of oral traditions in the context of change. The results of the study show that declarative utterances in both cultures not only serve to convey information, but also act as advice, exhortation, and reinforcement of social values in a positive manner. Through the use of metaphors, collective statements, and traditional expressions with layered moral meanings, positive and negative politeness strategies dominate the new types of politeness. Theoretically, this study reinforces the idea that the function of utterances can change according to the socio-cultural context and that the concept of politeness can be expanded in pragmatic research by considering the culture of the archipelago. The results of this study confirm that oral traditions are an important tool for maintaining social balance and preserving local wisdom. In addition, oral traditions have an impact on character education, cultural preservation, and language development in society. Keywords: Language politeness, spoken tradition, Minangkabau, Bali, intercultural pragmatics.